INVESTIGATION OF STRESS ON MULTI-LEVEL SHAFT USING FINITE ELEMENT METHOD BASED ON COMPUTER-AIDED ENGINEERING - Chandra, Hendri; Putra, Dicky Pratama; Romli, Romli (AUSTENIT, 2021)
The shaft is a rod that is part of the engine element with a circular cross-section that functions to move rotation without continuing power. Research on the stress concentration factor on the shaft continues to be developed significantly to mitigate torsional loads, bending loads, and axial loading. This study investigates the stress on a multilevel shaft using three methods: the engineering design method, simulation method, and analysis using the finite element method to obtain the investigated stress value based on computer-aided engineering. The material used in the shaft test is AISI 1020 steel with two research variables, namely, the independent variable with radius (mm); 0 mm, 2 mm, 6 mm, 10 mm, 20 mm, 50 mm, and the dependent variables are von mises and displacement. Based on the results of the test investigations that have been carried out by simulating the shaft, it can be concluded that the addition of radius material as the investigated variable by applying a torque of 50 N.m will reduce the stress on the shaft, and this does not apply to the displacement that occurs on the shaft when the force or load is working.